Is Grassfed Meat and Dairy Better for Human and Environmental Health? - Provenza, Frederick D.; Kronberg, Scott L.; Gregorini, Pablo (Frontiers in Nutrition, 2019)
Diets link the health of soil and plants with animals and environments. The global shift to diets high in processed foods, refined sugars and fats, and meat has contributed to 2.1 billion people becoming overweight or obese and to the incidence of type II diabetes, heart disease, and some cancers. If unimpeded, these dietary trends will be a major contributor to a projected 80% increase in agricultural greenhouse gas (GHG) emissions from food production and land clearing by 2050. Globally, agriculture contributes 25% to GHG emissions; of that total, meat and milk are 14% and grazing is 2.8%. While only 4% of meat and milk comes from grassfed livestock, livestock grazing can deliver a sizable share of climate mitigations. Of 80 ways to mitigate climate change, silvopasture ranks ninth, regenerative agriculture ranks eleventh, and managed grazing ranks nineteenth. The health of soil, plants, herbivores, and climate can be improved when erosion-prone cropping systems are replaced by pastures where livestock graze phytochemically rich mixtures of grasses, forbs, shrubs, and trees. In turn, some phytochemicals protect meat and dairy from protein oxidation and lipid peroxidation that cause low-grade systemic inflammation implicated in heart disease and cancer in humans. Phytochemical richness of herbivore diets increases as botanical diversity rises from livestock fed cereal grains in feedlots to grain-pasture mixes to botanically diverse pastures and rangelands. Nevertheless, epidemiological and ecological studies critical of red meat consumption do not discriminate among meats from livestock fed high-grain rations versus livestock foraging on pastures varying in phytochemical richness. We found much circumstantial evidence to support the hypothesis that biochemical richness of meat and dairy is important for human and environmental health. Future studies should elucidate how plant diversity affects phytochemical richness of herbivore diets; how that influences flavor and biochemical richness of meat and dairy; and how that affects health of people and the planet. Findings from these studies would help researchers and consumers understand how the foods we eat reflect our relationships with landscapes, waterscapes, and airscapes, manifest through phytochemical diversity, thus revealing how palates link soil, plants, herbivores, humans, and environments.